2015
DOI: 10.6004/jnccn.2015.0150
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Gene Expression Profiling for Breast Cancer in US Oncology Practice for Women Younger Than 65 Years

Abstract: Background Four practice guidelines incorporate the use of gene expression profiling (GEP) tests for early-stage, hormone-receptor positive, HER2 negative breast tumors. Few studies describe factors associated with GEP testing in US oncology practice. We assessed the relationship between clinical, demographic, and group-level socioeconomic variables and test use in women under age 65. Patients and Methods Data from five state cancer registries were linked with insurance claims data and GEP test results. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…This, in light of our findings of significantly higher initiation rates among tested vs. untested women, implies lower quality of care and non-adherence to clinical guidelines in the care of some women. Alternately, these differences in the tested vs. untested group may reflect a strong selection effect for testing, as we have previously reported that clinical markers were strongly associated with test use [10]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This, in light of our findings of significantly higher initiation rates among tested vs. untested women, implies lower quality of care and non-adherence to clinical guidelines in the care of some women. Alternately, these differences in the tested vs. untested group may reflect a strong selection effect for testing, as we have previously reported that clinical markers were strongly associated with test use [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Details of data linkages have been presented previously [10]. Briefly, our linked database consists of five state cancer registries containing clinical and pathological variables linked with claims data from HealthCore’s Integrated Research Database (HIRD SM ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple recent studies demonstrate continued adoption of genomic testing in breast cancer treatment decision making [57]. As research continues on the clinical utility of genomic tests, significant challenges arise in effectively communicating this risk information to patients and integrating this information with patient preferences to inform treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies have measured disparities in uptake by patients of Hispanic ethnicity, with some findings showing decreased use 24 and others reporting no difference compared with non-Hispanic whites. 25 Other studies of access to healthcare have found that Hispanics in the United States experience decreased access to care, similar to African Americans. 26,27 To address these contradictory findings and gaps in the research, recent population-based data are needed.…”
mentioning
confidence: 96%